Managing drugs in the prisoner society: heroin and social order in Kyrgyzstan’s prisons - Slade, Gavin (Punishment & society, 2022)
Through the case study of Kyrgyzstan this paper argues that a rapidly increasing availability of drugs in prison is not necessarily deleterious to solidarity and inmate codes. Instead, the fragmentary effect of drugs depends on the forms of prisoner control over drug sale and use. In Kyrgyzstan, prisoners co-opted heroin and reorganized its distribution and consumption through non-market mechanisms. State provision of opioid maintenance therapy incentivized powerful prisoners to move to distributing heroin through a mutual aid fund and according to need. Collectivist prison accommodation, high levels of prisoner mobility and monitoring within and across prisons enabled prisoners to enforce informal bans on drug dealing and on gang formation outside of traditional hierarchies. We argue that in these conditions prisoners organized as consumption-oriented budgetary units rather than profit-driven gangs.